Bhārata aura Dakshiṇa-Pūrvī Eśiyā : sāṃskrtika sambandha kī kahānī - Upādhyāya, Bharatasiṃha, 1915-1990 (SAMP early 20th-century Indian books project ;)
Cultural relations between India and Southeast Asia.